Differences in the reduction of bioaerosol bacterial colonies in preprocedural oral rinse using chlorhexidine gluconate 0,2% and povidone iodine 1% during ultrasonic scaling procedure: Experimental study - Khairiah, Arifatul; Malinda, Yuti; Suciati, Ame (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Dentists frequently come into direct or indirect contact with microorganisms from patients. Bioaerosols are formed during dental procedures involving rotary instruments. Infection control measures in dental practice are crucial to prevent cross-infection. Preprocedural oral rinsing is an infection control measure performed on patients before clinical procedures. This study aims to evaluate the difference in the reduction of bacterial bioaerosol counts using 0.2% Chlorhexidine Gluconate (CHX) and 1% Povidone Iodine (PV) as preprocedural oral rinses. Methods: The study used an experiment with a randomized controlled clinical trial (RCT) method involving 14 systemically healthy scaling patients diagnosed with gingivitis. Agar plates were positioned in three locations: the patient's chest, the dentist, and the assistant. Ultrasonic scaling was performed for 5 minutes without rinsing. Subjects were divided into two groups: patients who rinsed with 0,2% CHX and patients rinsing with 1% PV for 30 seconds. Agar plates were placed in the same three locations, and ultrasonic scaling was continued for 5 minutes. The agar plates were incubated at 36°C for 24 hours, and bacterial colonies were counted. Results: The number of bioaerosol bacterial colonies on agar plates placed on the patient's chest and the assistant decreased after rinsing with 0.2% CHX and 1% PV. Chlorhexidine gluconate reduced bacterial colonies by 17,11%, while povidone iodine increased it by 3,19%. There was a significant difference before and after rinsing with 0,2% CHX at all locations (p<0.05), while 1% PV showed no significant difference (p=0,182). Conclusion: Rinsing with 0,2% Chlorhexidine Gluconate reduces the number of bacterial bioaerosol colonies during ultrasonic scaling compared to povidone iodine.KEY WORDS: bioaerosol, preprocedural oral rinse, mouth rinses, ultrasonic scalingPerbedaan penurunan jumlah bakteri bioaerosol dalam tindakan preprocedural oral rinse menggunakan klorheksidin glukonat 0,2% dan povidone iodine 1% pada prosedur skeling ultrasonikABSTRAKPendahuluan: Dokter sering kali bersentuhan langsung atau tidak langsung dengan mikroorganisme dari pasien.Bioaerosol terbentuk selama prosedur gigi yang melibatkan rotary instrument. Langkah-langkah pengendalian infeksi dalam praktik kedokteran gigi sangat penting untuk mencegah infeksi silang. Preprocedural oral rinse merupakan salah satu langkah pengendalian infeksi yang dilakukan pada pasien sebelum tindakan klinis.Penelitian ini bertujuan menilai perbedaan penurunan jumlah bakteri bioaerosol dalam tindakan preprocedural oral rinse menggunakan Klorheksidin Glukonat (CHX) 0,2% dan Povidone Iodine (PV) 1%. Metode: Penelitian eksperimen dilakukan menggunakan metode randomized controlled clinical trials (RCT) yang melibatkan 14 subjek pasien skeling yang sehat secara sistemik dengan diagnosis gingivitis. Lempeng agar diposisikan di tiga lokasi yaitu, dada pasien, dokter gigi, dan asisten. Kemudian dilakukan skeling ultrasonik selama 5 menit tanpa berkumur. Subjek dibagi menjadi dua kelompok yaitu, pasien yang berkumur dengan CHX 0,2% dan pasien yang berkumur dengan PV 1% selama 30 detik. Lempeng agar ditempatkan pada tiga lokasi yang sama, dan skeling ultrasonik dilanjutkan selama 5 menit. Lempeng agar diinkubasi pada suhu 36°C selama 24 jam dan koloni bakteri yang terbentuk dihitung. Hasil: Jumlah koloni bakteri bioaerosol pada lempeng agar yang ditempatkan di dada pasien dan asisten menurun setelah berkumur dengan CHX 0,2% dan PV 1%. Klorheksidin glukonat menurunkan jumlah koloni bakteri sebesar 17,11%, sementara povidon iodine meningkat 3,19%. Terdapat perbedaan signifikan sebelum dan sesudah berkumur CHX 0,2% di semua lokasi (p<0,05), sedangkan PV 1% tidak menunjukkan perbedaan signifikan (p=0,182). Simpulan: Berkumur dengan klorheksidin glukonat 0,2% dapat menurunkan jumlah koloni bakteri bioaerosol saat skeling ultrasonik dibandingkan povidone iodine.KATA KUNCI: bioaerosol, preprocedural oral rinse, obat kumur, skeling ultrasonik